Glucose-1-phosphate as a selective substrate for enumeration of Bacteroides species in the rumen. - Dehority, B A (1977)
When glucose-1-phosphate was used as the only added energy source in a selective roll tube medium, colony counts for rumen contents ranged from 17.8 to 84.8% of the total culturable count. Percentages were highest in rumen contents from sheep fed high-concentrate rations. From a total of 73 cultures isolated from glucose-1-phosphate roll rubes, only 15.1% were presumptively identified as Bacteroides species. Strains presumptively identified as Butyrivibrio, Selenomonas, Treponema, Streptococcus bovis, and Lachnospira also fermented glucose-1-phosphate. Thus, glucose-1-phosphate would not be useful as a selective substrate for isolation or enumeration of Bacteroides species from the rumen.